Knowledge of Supplementary Foods on Behavior in Infants 0-6 Months in Sigenti Village, Parigi Mautong Regency Central Sulawesi Province - Erma Retnaningtyas; Ririn A Mardjengi (PT. Griya Eka Sejahtera, 2020)
Background: One of the problems that are often encountered in the community is the provision of additional food to infants before the baby is 6 months old. There is a community habit to give rice, bananas at the age of a few days, there is a danger, because the digestive tract in infants is not yet perfect. Method: The design of this research is correlational research with cross sectional approach. Respondents were taken by accidental sampling technique. The population studied were all mothers of infants 0-6 months in Sigenti Village with a sample of 30 mothers. Results: The results were analyzed using the Spearman Rank statistical test. The results showed that knowledge about food additives was known to almost all respondents in the Good category as many as 25 (83%) respondents. Behavior in Infants 0-6 Months, it is known that almost all respondents are in the Good category as many as 23 (77%) respondents. The results of data analysis show that the significance level is 0.000 < = 0.05 so that H0 is rejected and H1 is accepted. Conclusion: There is a Relationship between Knowledge of Supplementary Food and Behavior in Infants 0-6 Months in Sigenti Village, Parigi Mautong Regency, Central Sulawesi Province